In Search of a Polish Interest Representation Pattern in the European Union – The Case of Sector Interest Organisations - Kurczewska, Ursula (Studies of Transition States and Societies, 2010)
It may be expected that along with Poland’s accession to the EU, domestic sector interest organisations, to a larger extent than hitherto, will also be lobbying at the EU level, by using various ‘channels of access’. This article has two objectives: first, it is aimed at reconstructing the pattern of interest representation of Polish third sector organisations at the EU level; second, it analyses whether and how the isolated scheme fits into a pluralistic economic interest intermediation system in the EU. The analysis of individual cases reveals the advantage of a non-corporation related model in the representation of Polish interest groups, with the government occupying a dominant role, which may not be in line with the pluralistic and network-dependent character of the system at the EU level.